Thoharoh Dalam Al-Qur’an: (Kajian Tafsir Tahlili Surat Al-Maidah Ayat 6 Tafsir Al-Azhar) - Khairani, Naila; Feby, Novandasabina (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
When someone has reached the age of puberty, they are considered religiously mature and are expected to understand the obligations in Islam, including performing prayers regularly according to the specified times and procedures. One of the important preparations before performing prayer is performing ablution, tayammum, or obligatory bathing. In the study of this verse, it states that purification is one of the valid requirements for performing prayer. "Purifying" in this context refers to ritually cleansing oneself before performing prayer. This paper uses an approach that combines fact study through secondary sources with analysis using jurisprudence. The science of jurisprudence is used as an analytical tool based on the views of scholars from various schools of thought, which are selected based on the strength of their arguments. With Tafsir Al-Azhar, this research is focused on examining fiqh education in Surah Al-Maidah verse 6. This verse contains procedures for purifying oneself before praying. before praying, as well as providing a deeper understanding of the spiritual meaning behind the procedure.